MODEL OF MURAL PAINTING IN THE INPATIENT ROOM OF FATMAWATI HOSPITAL - Wiratno, Tri Aru (International Review of Humanities Studies, 2020)
The research model of mural painting in the children's ward of Fatmawati Hospital is interesting not only as a beauty but also the beauty it gives to patients. The model of mural painting as a form of instrumenta art works that aims and serves as the beauty of a child's inpatient room to further provide calm, coolness and peace to the pediatric inpatients. By using Terry Barrett's interpretation research method, the interpretation research method must include the contextualization of substantial creative work. And the development model of Borg and Gall, Dick and Carey. As a method that is integrated as a representation of mural painting. Thus the study would like to see interpretations and models of mural paintings in inpatients at Fatmawati Hospital, as part of direct treatment that can alleviate and provide healing to patients indirectly. The model of mural painting in the children's ward of Fatmawati Hospital is part of the value of painting that has an influence on pediatric patients in the inpatient room. Conclusion The model of the value of mural painting as part of identity, sign and character as well as part of participation in involving the public in an awareness of the beauty of mural painting as a value of socio-cultural reality. The value model of mural painting is based on the ability of affective aspects, where the experience of taste and spirit becomes a strength in providing life force for children.